1988
DOI: 10.1063/1.341167
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic studies of thin metallic films (invited)

Abstract: Anomalous metamagnetic-like transition in a FeRh/Fe3Pt interface occurring at T ≈ 120 K in the field-cooledcooling curves for low magnetic fields AIP Advances 2, 032168 (2012) Electric-field-control of magnetic anisotropy of Co0.6Fe0.2B0.2/oxide stacks using reduced voltage J. Appl. Phys. 112, 033919 (2012) Observation of intriguing exchange bias in BiFeO3 thin films J. Appl. Phys. 112, 033915 (2012) Rotary transportation of magnetic nanoparticle chains on magnetic thin film array A computer simulation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(84 citation statements)
references
References 18 publications
6
77
0
1
Order By: Relevance
“…On the other hand, the values of normalised coercive force HclH k grain generally indicates the stren~th of intergranular exchange coupling [4,5]. The HeI Hkgram value of the present samples is almost a constant of 0.05-0.07.…”
Section: Ill Results and Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…On the other hand, the values of normalised coercive force HclH k grain generally indicates the stren~th of intergranular exchange coupling [4,5]. The HeI Hkgram value of the present samples is almost a constant of 0.05-0.07.…”
Section: Ill Results and Discussionmentioning
confidence: 58%
“…The HeI Hkgram value of the present samples is almost a constant of 0.05-0.07. This suggests that the degree of intergranular magnetic coupling does not change remarkably against TA' It should be mentioned here that these values of HclH k gralO are a few times smaller than that of Co based thin film media (4], and several times smaller than the simulated value for the ideal media with no intergranular exchange coupling (HclHkgrain = about 0045) [2,5]. This result means that there is still a certain strength of intergranular exchange coupling.…”
Section: Ill Results and Discussionmentioning
confidence: 68%
“…As can be seen, there is rather good agreement between experimental and calculated data for this magnetically isotropic sample. The only noticeable discrepancy is that the squareness of the experimental loop is slightly higher than the model one, which has been assigned to intergranular interactions, 14 which were not taken into consideration in our calculations.…”
Section: Fig 3 Experimental In-plane Hysteresis Loopsmentioning
confidence: 67%
“…The segregation to two crystalline phases with the same d-spacing is equivalent to a single phase inhomogencous alloy. Since Cr did not preferentially segregate to grain boundaries, a resultant higher magnetic exchange coupling [20] and reduced magnetocrystalline anisotropy constant [21] would reduce the coercivity. Since Pt is known to increase the local disorder and thus coercivity by increasing the magnetocrystalline anisotropy [22], the lower coercivity of 60 nm film [5] suggested that less Pt existed in the CoCrPt (002) Bragg peak, compared with that of 30 nm film.…”
Section: Resultsmentioning
confidence: 99%